POTENSI AKTIVITAS ANTIBAKTERI DARI FRAKSI ETIL ASETAT DAUN JAMBU AIR [Eugenia aqueum (Burn F.) Alston] TERHADAP STHAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI - Ratu Choesrina; Suwendar Suwendar; Lanny Mulqie; Dieni Mardliyani (Universitas Islam Bandung, 2019)
Staphylococcus aureus (S. Aureus) is a constituent of the Gram positive type of normal flora. But if the amount is excessive it will become a pathogen in humans. Likewise with Escherichia coli (E. coli) which is a gram negative bacterium.Antibacterials that are available generally have a broad spectrum, so that side effects can damage normal flora if used long-term, according to the results of a study by Hariyati et al. The ethanol extract has great potential as an antimicrobial source. flavonoids, phenolic compounds and tannins have antibacterial properties. This antibacterial activity test uses agar diffusion method with wells to determine MIC, work spectrum, and work type against test bacteria (with turbidimetry method), the series of ethyl acetate fraction concentrations used is 50%; 25%; 12.5%; 6.25%; 3.13%; 1.56%; 0.78%; 0.31%. Then compared with the comparative antibiotic tetracycline using regression analysis. Ethyl acetate fraction of guava leaves has anti-bacterial activity against S. aureus and E. coli with KHM values of 12.50%. The working type of ethyl acetate fraction tends to be bactericidal in both S. aureus and E. coli. Equality of activity against S. aureus from 1 g of ethyl acetate fraction to tetracycline was 0.0295 g whereas for E. coli it was 0.0186 g.Keywords: antibacterial, Staphylococcus aureus, Escherichia coli